Lacunar infarcts in polycythaemia with raised packed cell volumes. Issue 6397 (1st October 1983) - Pearce, J M; Chandrasekera, C P; Ladusans, E J
Abstract : Lacunar (small deep cerebral infarcts) infarction is described in association with raised packed cell volumes. Two patients had polycythaemia vera, one stress polycythaemia. They presented with transient ischaemic episodes and were shown by computed tomography to have lacunes deep in the basal ganglia and internal capsule. Such lesions may be caused by small vessel occlusions related to increased viscosity and impaired oxygen consumption by adjacent tissues. Finding a raised packed cell volume in patients with lacunes and transient ischaemic attacks offers a further possibility of treatment.